1990
DOI: 10.1111/j.1476-5381.1990.tb12700.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diltiazem on calcium concentrations in the cytosol and on force of contractions in porcine coronary arterial strips

Abstract: 1 Using front-surface fluorometry with fura-2-loaded porcine coronary arterial strips, we simultaneously measured effects of a Ca2+ antagonist, diltiazem, on cytosolic Ca2+ concentrations ([Ca2+]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 40 publications
2
82
0
Order By: Relevance
“…The Ca2l sensitivity of the contractile regulatory apparatus (i.e. the [Ca2J]i-force relationship) is modulated by agonists (Morgan & Morgan, 1984;Hirano et al, 1990), coupled to G-proteins (Nishimura et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The Ca2l sensitivity of the contractile regulatory apparatus (i.e. the [Ca2J]i-force relationship) is modulated by agonists (Morgan & Morgan, 1984;Hirano et al, 1990), coupled to G-proteins (Nishimura et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…When tissues were exposed to 10;EM H-7, the Ca2"-independent contraction induced by sarafotoxin after a 60 min exposure to Ca2"-free solution was inhibited by 83.6 ± 3.7% (n = 3). (Figure 7) was similar to the pCa-force relationship noted with skinned arterial fibres of various species and organs Saida & Nonomura, 1978;Kuriyama et al, 1982 (Rasmussen et al, 1987;Murphy, 1989 Hirano et al, 1990). In the present study, we used front-surface fluorometry of fura-2 loaded rat aortic strips to examine the roles of extracellular and intracellular Ca2" and of the [Ca2+]J-force relationship in contractions induced by sarafotoxin.…”
Section: Tissue Preparationmentioning
confidence: 99%
“…It has been reported that endothelin also evokes a Ca2l-independent, transient contraction in porcine coronary arterial strips (Kodama et al, 1989). The (Hirano et al, 1990). It was suggested (Schichtele et al, 1989) that diltiazem might have no direct effect on the Ca2"-sensitivity of contractile elements.…”
Section: Effects Of Depletion Of the Caffeine-sensitivementioning
confidence: 99%
See 2 more Smart Citations